Peran Pembina Remaja untuk Perkembangan Perilaku Remaja di Jemaat GMIM Golgota - Spenerhard Makahinsade (EUANGGELION: Jurnal Teologi dan Pendidikan Kristen, 2023)
Abstract: This paper is a theological analysis for holding a youth worship meeting which is held once every two weeks face to face. So the authors want to conduct research scientifically by studying the "Role of Youth Coaches for the development of the behavior of the GMIM Golgotha Youth congregation For Youth Fosters, Youth Fosters. Youth Coaches have a very strategic role to be able to develop potential in the future growth and development of Youth. However, youth coaches must have very specific requirements or criteria, namely a youth coach before entering the world of youth service is someone who already has a new life, meaning that a youth coach has had a new life first. So that the life of a youth coach will become a role model or role model / public figure for their students. With the way of life that is shown in the daily life of youth guidance, such as diligently reading the Bible, diligently praying and diligently participating in fellowship, it will become a living sermon for the lives of teenagers, because strong preaching today is no longer in the form of advice / words but is the behavior / behavior displayed by the youth coach. This study uses a descriptive qualitative approach, where the data obtained is in the form of explanations of concepts or text and not numbers. The results of the study concluded that the role of youth coaches for the development of adolescent behavior is able to develop behavioral potential to shape the character of adolescents by building all abilities and abilities of youth coaches by building partnerships related to all aspects of church service in a holistic manner."